2020
DOI: 10.1371/journal.pone.0237507
|View full text |Cite|
|
Sign up to set email alerts
|

Figures of merit and statistics for detecting faulty species identification with DNA barcodes: A case study in Ramaria and related fungal genera

Abstract: DNA barcoding can identify biological species and provides an important tool in diverse applications, such as conserving species and identifying pathogens, among many others. If combined with statistical tests, DNA barcoding can focus taxonomic scrutiny onto anomalous species identifications based on morphological features. Accordingly, we put nonparametric tests into a taxonomic context to answer questions about our sequence dataset of the formal fungal barcode, the nuclear ribosomal internal transcribed spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(87 reference statements)
0
3
1
Order By: Relevance
“…This classification is consistent with some previous studies [ 1 , 3 ]. Our phylogenetic analysis supports a sister relationship between Gomphus and Turbinellus , contrasting with those studies in which Turbinellus , together with two or more genera of Gomphaceae, were found to be sisters to either Gomphus alone or Gomphus together with several species of Ramaria [ 2 , 63 , 64 , 65 ]. The previous definition of gomphoid fungi [ 1 ], including Gloeocantharellus , turned out to be unnatural.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This classification is consistent with some previous studies [ 1 , 3 ]. Our phylogenetic analysis supports a sister relationship between Gomphus and Turbinellus , contrasting with those studies in which Turbinellus , together with two or more genera of Gomphaceae, were found to be sisters to either Gomphus alone or Gomphus together with several species of Ramaria [ 2 , 63 , 64 , 65 ]. The previous definition of gomphoid fungi [ 1 ], including Gloeocantharellus , turned out to be unnatural.…”
Section: Discussioncontrasting
confidence: 99%
“…Gomphus harbors conspicuous members of Gomphaceae and are often confused with other genera in the family. Recent analyses [ 3 , 63 , 64 , 65 ] indicated that Gomphus, in its broader sense, constitutes a paraphyletic group of fungi with Ramaria sensu lato. To maintain the monophyly of Gomphus , some species were transferred to Gloeocantharellus , and Turbinellus was resurrected [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morpho-anatomical features are insufficient to identify a mushroom species. Fifteen species of Ramaria were identified and characterized by Martin et al (2020) using combined morphological and molecular data. In conclusion, R. barenthalensis is recorded as a new coralloid fungus to the state of Jammu and Kashmir, Pakistan based on morpho-anatomical and molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Quél., are common edible coralloid fungi (Krupodorova and Sevindik 2020). Ramaria species have been identified through scanning electron microscopy and molecular techniques by Martin et al (2020). Internal transcribed spacer (ITS) restriction length polymorphism was observed among Ramaria species and used as a diagnostic tool for characterization (Nouhra et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that both morphometric data and molecular methods were effective in the identification of A. fumigatus (GenBank accession KU321562.1), A. flavus (GenBank accession MH270609.1), A. niger (GenBank accession MK452260.1), and P. chrysogenum (GenBank accession MK696383.1). Utilizing ITS rDNA sequence similarity (95%) to establish species boundaries operationally, a total of 277 fungal species were identified from 1,403 endophytic strains isolated from various common plants across arctic, boreal, temperate, and tropical regions, representing a wide range of phylogenetically diverse plant taxa [37].…”
Section: Molecular Identification and Dnamentioning
confidence: 99%